Comparison of the effectiveness of emotion-focused therapy (EFT) with metacognitive therapy (MCT) on emotional-social competence of 13- to 18-year-old male students in divorced families - Mohammad Parnov; Abdolmajid Bahrainian; Fatemeh Shahabizadeh; Saied Malihialzackerini (مجله علوم روانشناختی)
Background: Some studies have shown that parent’s divorce could weaken the social-emotional competence among teenagers. Previous studies have confirmed the effectiveness of psychological interventions. However, no research has been found comparing the effectiveness of Emotion-Focused Therapy and Metacognitive Therapy. Aims: The present study aimed to compare the effectiveness of Emotion-Focused Therapy with Metacognitive Therapy on the emotional-social competence of 13 to 18-year-old male students from divorced families. Methods: The research was a semi-experimental design of pre-test, and post-test type with a three-month follow-up. The statistical population of the research included boys between the ages of 13 and 18 years old in two high schools in the fifth district of Tehran in the academic year 2021-2022. By random sampling, 45 people were selected as a statistical sample in two experimental groups and one control group. Zhou, M. and Ee, J. (2012) Social-Emotional Competence Questionnaire was used for data collection. Also, emotion-focused therapy (Greenberg, 2015) was implemented in eight sessions in the first experimental group and metacognitive therapy (Jelinek et al., 2020) was implemented in eight sessions in the second experimental group. Still, the members of the control group did not receive any treatment intervention. Analysis of variance with repeated measures, Bonferroni post hoc test, and SPSS-26 software were used to analyze the data. Results: The research findings showed that the effectiveness of Metacognitive Therapy and Emotion-Focused Therapy on the components of “self-awareness, social awareness, and self-management” of the dependent variable was significant (p<0.01). Also, statistically, there was no significant difference in terms of effectiveness between the two treatment methods. Conclusion: According to the research findings, it can be concluded that Emotion-focused Therapy and Metacognitive Therapy both improve the social-emotional competence of adolescent boys aged 13 to 18.